Models of Workplace Well-Being in Sandwich Generation Female Leaders: A Literature Review and Research Proposal - Sudarji, Shanty; Dwi Riyanti, Benedicta Prihatin; Dahesihsari, Rayini (Faculty of Psychology Universitas Gadjah Mada, 2025)
Female leaders from the sandwich generation face challenges not only in the workplace but also in their domestic roles. They have multiple roles simultaneously, such as being parents and children, each with different role demands. This study aimed to review the literature on wellbeing at work and evaluate the extent to which the literature on this topic covers the issue related to female leaders of the sandwich generation. The literature reviewed in this research was articles published in accredited and reputable journals, using quantitative and qualitative research methods, as well as research within the organizational scope. The study found several variables that were positively related to wellbeing at work, including personality type, resilience, work-life balance, perceived organizational support, social support, coping strategies, organizational culture, and cognitive flexibility. The findings indicate that work-life balance is often positioned as a key factor directly influencing wellbeing. However, many studies also highlight its role as a mediator in the relationship between both internal and external predictors and wellbeing. Given the importance of work-life balance for female leaders in the sandwich generation, the researchers proposed a model that emphasizes factors receiving less attention in workplace well-being research but are critical for this group. Specifically, the researchers suggested that cognitive flexibility and creative adaptability are important internal factors, while perceived organizational support is a key external factor affecting the wellbeing of sandwich generation female leaders. In this model, work-life balance mediates the influence of these factors on wellbeing.